(3QSGdI GdMOjK GdCQHYjfs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMOjK GdChd Gddge dGNjQ EdG NjQc hdG WjQ EdG hdG Zdg ZjQc CNQLg CMeO Hf YHO Gddg Hf YeQ eQahYkG hcPG CNQLg GdWHQGfi s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3aCbhd adeG SeYJ gfO cdeG GfTOJ hgd gfO GdCegQI ZQjHI Gde fWdbgG dhbJgG hhRf GdegQ eGFJi Cda OQge s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B30s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs